Association Between Platelet-to-Lymphocyte Ratio and Preterm Necrotizing Enterocolitis - Zheng, Juan; Wang, Hua (Frontiers in Pediatrics, 2021)
Background: Necrotizing enterocolitis (NEC) is a devastating process for very low birth weight infants. NEC is secondary to the complex interaction of multiple factors which results in intestinal mucosal damage and leads to intestinal necrosis. While because of the lack of sensitive laboratory indicators, making the diagnosis earlier should be very difficult. The purpose of this study was to investigate the relationship between NEC and the platelet to lymphocyte ratio (PLR) of preterm neonates, so as to help the neonatologists distinguish it more earlier. Methods: Retrospective case–control study. The preterm neonates who diagnosed with NEC from January 2018 to December 2019 in the West China Second University Hospital. For each neonatal intensive care unit (NICU) graduated with preterm, controls were selected (matched for gestation and year of birth)from preterm who diagnosed without NEC .This Retrospective study was conducted with 93 preterm neonates diagnosed with NEC compared with 107 matched controls without NEC . Exclusion criteria were postmaturity, small or large for gestational age according to the week of pregnancy, congenital major anomalies, and cyanotic congenital heart disease. Using Empowerstats analysis to identify association of PLR with preterm NEC. Results: A total of 200 preterm neonates were included in the study. Of these, 93 NEC and 107 matched controls without NEC, NEC group had significantly higher PLR levels compared with the control group. On univariate analysis, risk factors for NEC were PLR, C-reaction protein and preeclampsia of mother. On multivariate analysis, risk factors for NEC were PLR of＞100 within 1 week before NEC's diagnosis. There was a positive association between PLR and the preterm NEC group. A high PLR of ＞100 may be determined as the predictive cutoff value of preterm NEC group, it is associated with the occurrence of NEC as compared with other preterm neonates【OR:18.82(95% CI 2.93 to 120.98), P = 0.002】. Conclusions: PLR of ＞100 is associated with an increased risk of NEC in preterm neonates.